The relationship of plasma catestatin and heart rate variability parameters in middle-aged men with primary hypertension - E. Yu. Gubareva; N. N. Kryukov; I. V. Gubareva (Российский кардиологический журнал, 2019)
Aim. To study the catestatin plasma level in patients with primary hypertension of different cardiovascular risk and to assess its relationship with heart rate variability (HRV) parameters.Material and methods. One hundred eighty men aged 30-50 years were divided into groups: group 1 (n=28) — hypertensive patients with medium risk of developing cardiovascular complications (CVC), group 2 (n=76) — hypertensive patients with high risk of CVC, group 3 (n=31) — hypertensive patients with very high risk of CVC. The control group consisted of healthy men with normal blood pressure (BP) (n=45). We determined plasma catestatin (ng/ml) and conducted Holter monitoring.Results. A pattern was found to reduce the concentration of catestatin with increasing risk of CVC in hypertensive patients, but there were no significant differences between the studied groups (p>0,05).We determined corrections between catestatin levels and echocardiography thickness of left ventricular posterior wall (r=-0,523; p=0,045) and interventricular septum (r=-0,523, p=0,045) in diastole in group 2; thickness of left ventricular posterior wall (r=0,258; p=0,035) and interventricular septum (r=0,254; p=0,038) in systole in group 3. In patients of group 2, direct correlations of catestatin levels and sympathicotonia LF/HF were revealed during the whole observation period (r=0,301; p=0,019) and during wakefulness (r=0,308; p=0,019); inverse correlations — with parameters of parasympathetic tone: nHF during the whole observation time (r=-0,318; p=0,013) and during wakefulness (r=-0,342; p=0,007), pNN50 in the afternoon (r=-0,270; p=0,037).Conclusion. A decrease in catestatin concentrations in hypertensive patients is associated with the progression of disease and an increase in cardiovascular risk. It is assumed that catestatin is involved in the formation of HRV in patients with primary hypertension.